A functional polymorphism of TIR-domain-containing adaptor protein is not associated with axial spondyloarthritis. Issue 5 (11th December 2007) - Cantaert, T; Stone, M A; Borg, M ter; Mogg, R; De Vries, N; Wilson, A G; Tak, P P; Baeten, D
Abstract : Objective: A genetic variant of the toll-like receptor (TLR)2/4 adaptor protein TIRAP (single nucleotide polymorphism (SNP) C539T) was identified in a UK and in several African populations. The heterozygous genotype of this SNP has been associated with protection from severe infections. This allele results in an attenuated response to bacterial pathogens. As an exaggerated innate immune response to pathogens has been implicated in spondyloarthritis (SpA) pathogenesis, we analysed if the heterozygous C/T genotype was underrepresented in axial SpA compared with healthy controls. Methods: 204 patients with axial SpA and 175 population-matched controls were included. SNP C539T was determined with a sequence-specific polymerase chain reaction and direct sequencing. Results: The frequency of the haplotypes was similar in cases and controls (87% for C and 13% for T in both groups). The C/T genotype, which attenuates TLR signalling, was not underrepresented in cases versus controls (19% in controls vs 24% in cases, p = 0.44). The T/T genotype, was slightly lower in cases than in controls, although this was not significant (3.4% in controls vs 1% in cases, p = 0.15). Within the cases, there were no differences in disease phenotype or activity between patients with the C/C or C/T genotype. Conclusions: This study did not show significant associations of SNP S180L of the TLR2/4 adaptor protein TIRAP with axial SpA.